General Defenses under Law of Torts: An Analysis: Exploring Defenses in Tort Cases (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Plaintiffs in tort cases seek a private legal remedy, most often monetary compensation forlosses they have suffered. Similarly to criminal law, tort claims deal with state-sanctioned criminalmisconduct. A civil lawsuit and a criminal investigation are both possible outcomes in countries wherecivil and criminal justice systems are separate. Unlike contract law, tort law provides civil remedies in thecase of a breach of a contractual commitment nonetheless, tort and criminal law responsibilities aremore basic and are imposed regardless of whether the parties have a contract. In this paper discuss thereview of defenses under the law of torts, volenti non fit injuria, plaintiff being the wrongdoer, inevitableaccident, act of god vis major, statutory authority.